On The Form and Judgment Function of Sense of Language - Wenhua, Duan (Bina Nusantara University, 2014)
In parole communication, people are always able to judge whether othersâ€™ expressions are proper or not, understandableor not, elegant or not. In the field of teaching Chinese as a foreign language, teachers can also quickly point out the problems in studentsâ€™ expressions and writing. This kind of direct sense is called Sense of Language. Generally speaking, Sense of Language is considered as a kind of â€œability of subjective judgmentâ€. In fact, there is a guide behind Sense of Language, which is profound rational theory proved by Psychology and Cerebral Science. Sense of Language will be discussed carefully in this article.